A Study on Factors of Child Abuse from Reported Child Abuse Cases to THJ in Jaffna District, Sri Lanka - (2015-2016) - Sathasivam, S.A. (University of Jaffna, 2018)
- Introduction: Child abuse is a devastating global problem that is deeply rooted in cultural, economic and social practices. Since the child protection structures are undeveloped, the problem of child abuse rises significantly in Sri Lanka. Teaching Hospital, Jaffna (THJ) is the tertiary center for the Northern Province, which encompasses five districts Jaffna, Killinochchi, Mannar, Mullaitivu and Vavuniya. This study focuses on reported child abuse cases to the THJ for the years of 2015 and 2016.
Keywords: Child abuse; Jaffna district; Multinomial logistic model